2021
DOI: 10.2174/1874372202115010045
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Intima-Media Thickness in Patients with Psoriasis

Abstract: Introduction: Since the early 20th century, findings have demonstrated that psoriasis is frequently associated with atherosclerosis and cardiovascular diseases. The Carotid Intima-Media Thickness (CIMT) is a surrogate marker of atherosclerotic vascular disease. Objective: The aim of this study was to investigate the CIMT in patients with psoriasis and investigate its correlation with the clinical features. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…[ 6 ] In our study, three (9.37%) participants, including two males and one female, had CIMT ≥1 mm, with the mean value of CIMT being 0.70 ± 0.21 mm. Many previous studies[ 6 13 16 20 21 22 ] reported a similar range (0.61 mm to 0.84 mm) of values; some others, higher[ 23 24 25 26 ] (0.9 mm to 1.03 mm) and still others,[ 18 27 ] lower (0.5 mm).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…[ 6 ] In our study, three (9.37%) participants, including two males and one female, had CIMT ≥1 mm, with the mean value of CIMT being 0.70 ± 0.21 mm. Many previous studies[ 6 13 16 20 21 22 ] reported a similar range (0.61 mm to 0.84 mm) of values; some others, higher[ 23 24 25 26 ] (0.9 mm to 1.03 mm) and still others,[ 18 27 ] lower (0.5 mm).…”
Section: Discussionmentioning
confidence: 75%
“…A large number of earlier studies[ 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 ] reported higher prevalence of MetS ranging from 30% to 60% and increased sub-clinical atherosclerosis in psoriatic patients compared to age- and sex-matched controls. However, the assessment of sub-clinical atherosclerosis has been done in a few studies in patients of psoriasis with and without MetS.…”
Section: Discussionmentioning
confidence: 99%